Combined enzymatic and ultrasound-assisted aqueous two-phase extraction of antidiabetic flavonoid compounds from Strobilanthes crispus leaves - Arbianti, Rita; Angelina; Suryapranata, Bryan; Purwati Latifah, Linatri; Fadilah Putri, Najah; Surya Utami, Tania; Muharam, Yuswan; Slamet (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
A novel green extraction method combining enzymatic and ultrasound-assisted aqueous two-phase extractions was employed to enhance and purify the flavonoid extract from Strobilanthes crispus leaves. Cellulase was used in the pretreatment, and ethanol-(NH4)2SO4 was selected as the solvent. A concentration of 7% (w/w) cellulase and a duration of 2 h were the optimal conditions for pretreatment. The optimal conditions for ultrasound-assisted aqueous two-phase extraction were 33% (w/w) ethanol and 14% (w/w) (NH4)2SO4 as they produced a yield (77.81%), partition coefficient (31.17), extraction efficiency (98.04%), and a high total flavonoid content (0.3666 mg QE/g dry leaf powder). Six compounds from the leaf extract were identified through liquid chromatography-mass spectrometry/mass spectrometry-quadrupole-time of flight (LCMS/MS-Q-TOF) analysis. The crude extract and three compounds in it (kaempferol, graveobioside A, and genistein) showed an antidiabetic activity with IC50 values of 390.35, 201.87, 292.73, and 431.82 mg/mL, respectively. These values are comparable to the standard drug acarbose.